AM fungi modulate organic nitrogen preference of Eucalyptus to enhance seedling growth under low fertilization - Xinyue Li; Chunyu Huo; Xinzhu Yang; Qiutong Liu; Zijia Su; Xinyi Fan; Zhihong Liu; Zujing Chen; Zujing Chen (Frontiers in Plant Science)
IntroductionEucalyptus is one of the most productive trees, with short-rotation and high values. Fertilization and inoculating arbuscular mycorrhizal (AM) fungi can increase Eucalyptus productivity. Many studies have concentrated on plant absorption of inorganic nitrogen, but less on organic nitrogen and the effect of AM fungi on organic nitrogen acquisition. MethodsIn this study, we set 28 treatments including with or without Rhizophagus irregularis inoculation, three organic nitrogen sources (glycine, L-glutamine and peptone) and four levels of nitrogen and phosphorus fertilization, with no application of organic nitrogen fertilizer as control. Results and DiscussionThe results indicated that the height, ground diameter and crown width of Eucalyptus seedlings under 2.5 mM glycine and 0.3 mM Pi (G2P2) treatment were 3.23, 0.82 and 3.70 times higher than those without organic nitrogen under 0.03 mM Pi (N0P1) treatment, respectively. Inoculation with AM fungi contributed 10.85%-162.00% increase in dry weight compared to non-mycorrhizal (NM) treatments. Mycorrhizal seedlings also showed significantly higher total phosphorus contents, nitrogen use efficiency and activity of glutamine synthetase, relative to NM treatments. The relative expressions of genes related to organic nitrogen transport (EgAAP3, EgLHT1, EgProt2) and nitrate nitrogen transport (EgNPF4.5, EgNPF6.3, EgNPF8.1) were up-regulated in mycorrhizal Eucalyptus roots, compared to the NM treatment. Non-mycorrhizal Eucalyptus favored peptone, while mycorrhizal Eucalyptus preferred glycine. Eucalyptus growth under 2.5 mM organic nitrogen and 0.3 mM Pi (N2P2) treatments were promoted markedly, regardless of organic nitrogen source. Whereas, the growth of mycorrhizal Eucalyptus under 0.25 mM organic nitrogen and 0.3 mM Pi (N1P2) treatments were increased the most. This study explored the organic nitrogen and AM fungi fertilizer mode for Eucalyptus, this has potential to improve production practice of Eucalyptus under low nitrogen and phosphorus condition.